2014
DOI: 10.1007/s00436-014-4072-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and anthelmintic efficacy of topical eprinomectin in goats prevented from grooming

Abstract: Pharmacokinetics and anthelmintic activity of topical eprinomectin in goats prevented from physical contact to others and self-grooming were studied. Sixteen approximately 7 months old male castrated German White Noble goats harbouring induced infections of gastrointestinal nematode parasites were included in the study. They were blocked based on pre-treatment body weight (range 22.4 to 36.4 kg) and then randomly allocated to the untreated control group or the group treated with topical 0.5% w/v eprinomectin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
3
11
1
Order By: Relevance
“…In addition, there is also indication of efficacy of topical 0.5% w / v eprinomectin against Oestrus ovis nasal bot infestation [16, 17]. Overall, the therapeutic efficacy demonstrated in the present studies in sheep was very similar to the array of nematode parasites effectively treated by the administration of topical 0.5% w / v eprinomectin at 1 mg per kg body weight to goats [39, 40]. …”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In addition, there is also indication of efficacy of topical 0.5% w / v eprinomectin against Oestrus ovis nasal bot infestation [16, 17]. Overall, the therapeutic efficacy demonstrated in the present studies in sheep was very similar to the array of nematode parasites effectively treated by the administration of topical 0.5% w / v eprinomectin at 1 mg per kg body weight to goats [39, 40]. …”
Section: Discussionsupporting
confidence: 53%
“…40], T max appears to occur later in sheep, indicating slower absorption possibly due to the difference of the structure of the skin/hair coat characteristics between the two species. Overall, similar pharmacokinetic profiles were demonstrated for topical 0.5% w / v eprinomectin in sheep and goats which translate to a similar spectrum of anthelmintic activity in sheep (these Studies 1, 2 and 3) and goats [39, 40, 49]. …”
Section: Discussionmentioning
confidence: 68%
“…Oral, intramuscular, and intravenous pharmacokinetic data have also been reported for adult goats suggesting that the intravenous dose of 2.2 mg/kg is applicable for goats ( Konigsson et al, 2003 ). Other pour-on products such as topical eprinomectin have reported lower bioavailability in goats than in cattle ( Rehbein et al, 2014 ). Eprinomectin has a much lower plasma concentration in goats compared to cattle designated by lower C max and AUC indicating the recommended bovine dosage may not be adequate in caprine ( Alvinerie et al, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy studies, conducted in sheep ( Hamel et al, 2017 , Hamel et al, 2018 ), goats ( Rehbein et al, 2014 ) and cattle ( Rehbein et al, 2012 ), reported high anthelmintic efficacy of pour-on formulation of eprinomectin, at the recommended dosage, for each of the forementioned animal species. In our study, the efficacy of topically administered eprinomectin was also high (>90%) for the first 42 days post treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The anthelmintic efficacy of pour-on eprinomectin has been studied in sheep ( Hamel et al, 2017 , Hamel et al, 2018 ), goats ( Rehbein et al, 2014 ) and cattle ( Rehbein et al, 2012 ). However, there is no research establishing the association between treatment of nematode-infected dairy sheep with eprinomectin and their milk yield or somatic cell counts (SCC) in milk.…”
Section: Introductionmentioning
confidence: 99%